Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
17x + 3. ( -16x – 37) = 2x + 43 - 4x
<=>17x-48x-111=-2x+43
<=>-29x=154
<=> \(x=-\frac{154}{29}\)
-3. (2x + 5) -16 < -4. (3 – 2x)
\(\Leftrightarrow-6x-31< -12+8x.\)
\(\Leftrightarrow-14x< 19\Rightarrow x< -\frac{19}{14}\)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
a) 3x2 + 12x =0
<=> 3x( x+ 4)=0
<=> \(\orbr{\begin{cases}3x=0\\x+4=0\end{cases}}\) <=>\(\orbr{\begin{cases}x=0\\x=-4\end{cases}}\)
d) \(4x^3=4x\)
<=> \(4x^3-4x=0\)
<=> 4x( x2 -1) =0
<=> 4x ( x - 1) ( x+ 1) =0
<=> 4x=0 hoac x-1=0 hoac x+1=0
<=> x=0 hoac x=1 hoac x=-1
1. => -15x-30+14x-21 = -50
=> -x-51 = -50
=> -x = -50 + 51 = 1
=> x = -1
2. = >x.(x-2) = 0
=> x=0 hoặc x-2=0
=> x=0 hoặc x=2
3. => 8x^2+28 = 100
=> 8x^2 = 100-28 = 72
=> x^2 = 72 : 8 = 9
=> x=3 hoặc x=-3
Tk mk nha
Thăn kiu pạn nhaaaaaaaa